An alternative open architecture controller design for the Bioloid humanoid robot / ‘Aqilah Zainuddin … [et al.] - Zainuddin, ‘Aqilah; Ali, Badar; Ahmed, Mohamed; Md Zan, Md Mahfudz; Hashim, Habibah (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Robot-based assistive technologies have in recent times, become an important research topic. Most commercial robots come with control systems which may support several types of user inputs/outputs, but usually provide support for application-specific motion control. In developing high level robotbased assistive application, there is a need for more open scheme for controller design. In this paper, a Raspberry Pi-based controller intended to extend the features of the commercial Bioloid humanoid robot was designed to provide an openarchitecture alternative than its proprietary controller, the CM530. Given that the custom-designed controller is more open and provide greater flexibility to developers, a comparison is also made towards its ability to provide better support in terms of control perspectives. The custom-designed controller provides better capabilities regarding to its open-architecture which gives an opportunity for other developers to delve further into the structure knowledge that helps many aspects of application development. The open characteristics of proposed controller consequently will enhance the controller potential/capabilities and can be utilized by other robots in future. The outcome of the experiments revealed that the open control system provided by the Raspberry Pi platform has slightly higher average power consumption which is 2.04W difference from CM-530 controller during the idle mode of 18 servomotors, but is able to provides better capabilities. As for dynamic servomotors, the average power difference recorded for single servomotor motion is 3.08W and 9.3W for multiple servomotors. All results were calculated and graphed using MATLAB R2015a software.